The relationship between arm length and body mass index (BMI) with turbo-throwing performance in elementary school students - Putri, Awaliyah Riskyta; Nurrochmah, Siti (Physical Education and Sports: Studies and Research, 2025)
Background: This research is motivated by insufficient scientific research that specifically examines the relationship between arm length and Body Mass Index (BMI) on turbo throwing performance in elementary school students, especially in preparation for the National Student Sports Olympics (O2SN). Objectives: This study examines the relationship between arm length and BMI and the turbo-throwing performance of sixth-grade students of State Elementary School Bunulrejo 1 Malang in preparation for the National Student Sports Olympics (O2SN) in 2025. Methods: The method used is a quantitative descriptive design with a correlational study. The study population comprised 71 male students, with a sample of 45 male students. The research instrument was a turbo-throwing basic motion performance test, arm length measurement, and Body Mass Index (BMI) measurement. The analysis technique uses inferential statistics in the form of multiple correlation analysis, which is complemented by multiple regression analysis. Results: The results were obtained using inferential statistics through multiple correlation analysis. The results of the multiple correlation test obtained a coefficient value = 0.723 and Sig. P = 0.001 < a = 0.05, and the contribution of the variable effectiveness of arm's length to turbo-throwing performance is 46.3%, while BMI is 5.9%, so the variables arm length and BMI provide an effective contribution of 52.2%. Conclusions: Arm length and BMI significantly influence turbo-throwing performance. Arm length is the most dominant factor. These results can be a reference for teachers and coaches when selecting O2SNs and coaching athletes at the basic education level. Future researchers are expected to examine other variables that have not been studied to provide a more comprehensive picture of turbo-throwing performance.